The Role of Creative Industries in Economic Development: The Human Factor Development Approach - Matiza, Vimbai Moreblessing (African Journal of Inter/Multidisciplinary Studies, 2020)
In most cases economic development is measured using monetary value, in terms of Gross Domestic Product (GDPs), Gross National Product (GNPs), and per capita income. Economic development cannot only be associated with monetary figures. Against this aspect, creative industries are also a driving force in economic development. This paper demystifies the notion that economic development is hardly measured through art. Using the human factor development approach, this article debates the role of creative industries in economic development. This model assumes that human beings are an important component in enhancing economic development through the creative industry as it is a more sustainable approach. Sustainability is enhanced by incorporating personal and human efforts to define standards in terms of creativity, hence, contributing to sustainable economic development. Further, the article argues that the employment of human factor development to enhance economic development through creative industries is of paramount importance as it allows indigenous people to take part in the developmental process of their economies. Data were collected using a qualitative research methodology and a purposive sampling of selected art industries to establish the contribution of the creative industry to economic development.